Structure of domination and dynamics of activity of ground-beetles in agroecosistems of Derbent area - G. M. Nahibasheva; A. A. Bagomaev; R. A. Musaeva (Юг России: экология, развитие, 2015)
For the first time for area of research 61 kind of ground-beetles, concerning to 28 sorts and 13 vital  structure of ground-beetles of agroecosistems are studied. New data about structure and character biotopical are obtained distributions, seasonal dynamics of activity of ground-beetles. Phenological change prepotent of ground-beetles ofagroecosistems of Derbent area is revealed.